2021
DOI: 10.1177/23727322211032250
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity: What Are Its Effects, Why, and What Can Policy Do About It?

Abstract: Food insecurity—lack of access to sufficient food for an active and healthy lifestyle—affects more than 10 million children in the United States. Ample research links food insecurity to hampered child physical, cognitive, and social-emotional development and provides insights for policy. After introducing food insecurity and its measurement, this article summarizes what is known about the effects of food insecurity on child development. It then considers how food insecurity harms children and explores both dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 55 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…In addition, as the theoretical framework indicates, food insecurity is connected with one's health through parents' well-being and emotional status. Thus, the food assistance program should also help parents reduce stress and create favorable environments for child development [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, as the theoretical framework indicates, food insecurity is connected with one's health through parents' well-being and emotional status. Thus, the food assistance program should also help parents reduce stress and create favorable environments for child development [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that food insecurity was associated with depression, chronic diseases, cognitive impairment, and sleep disorders [15][16][17][18]. Food insecurity may invoke biological changes that have long-run health consequences or disrupt children's environments [17,19].…”
Section: Theoretical Framework and Literature Review 21 Theoretical F...mentioning
confidence: 99%
See 2 more Smart Citations
“…Food insecurity contributes to the “double burden of malnutrition” and can lead to both undernutrition [ 18 ] and child obesity [ 19 ], as it is linked to unhealthy eating habits [ 20 ], including reduced fruit and vegetable intake [ 21 ] and a higher likelihood of consuming sugar-sweetened beverages [ 22 ]. In addition, food insecurity during childhood is associated with poor health outcomes, including higher risk of anemia, chronic illness, and hospitalizations [ 23 ], as well as social and emotional problems [ 24 , 25 ] and impaired academic success [ 25 , 26 ].…”
Section: Food Insecurity In Early Childhoodmentioning
confidence: 99%